Attitudes and subjective norms towards social media influencers with behavioural intent on food choices among undergraduate Students In School Of Health Sciences, Universiti Sains Malaysia (USM), Health Campus, Kubang Kerian, Kelantan - Bakri, Syafini (Universiti Sains Malaysia, 2024)
This study investigates the influence of social media influencers (SMIs) on the dietary choices of undergraduate Health Sciences students at USM Health Campus. It examines the relationship between students' attitudes, subjective norms towards SMIs, and their behavioral intent regarding food choices. Using correlation and regression analyses, 90 respondents participated in the study. The majority of respondents were female (77.8%), aged 21-23 (76.7%), and Malay (80%). While a positive correlation was found between attitude and behavioral intent, regression analysis showed no significant relationship (β = 0.056, p = 0.504). Subjective norms demonstrated a significant relationship with behavioral intent (β = 0.680, p < 0.001), indicating social pressure plays a greater role in dietary choices than personal attitudes. The study's strengths include a focused sample and validated instruments, with future recommendations suggesting a broader sample and longitudinal design.